THE CORRELATION BODY MASS INDEX WITH BLOOD PRESSURE ON ELDERLY IN PERERENAN VILLAGE OF MENGWI SUB-DISTRICT OF BADUNG REGENCY - Rastiti, Putu Dita; Andayani, Ni Luh Nopi; Tianing, Ni Wayan (Majalah Ilmiah Fisioterapi Indonesia; Vol 6 No 1 (2018): Majalah Ilmiah Fisioterapi Indonesia, 2018)
Decreased metabolic processes in the elderly followed by decreased physical activity, causing the addition of calories to be converted into fat resulting in overweight. Overweight is one factor that can affect blood pressure and trigger hypertension, so conducted research to determine the relationship between body mass index with blood pressure in the elderly. A cross sectional analytic study with elderly research sample in Pererenan Village of Mengwi Sub-district of Badung Regency was 104 people selected according to inclusion and exclusion criteria. The results showed a significant correlation between body mass index and blood pressure in elderly (p <0.05) and the results showed a thin BMI (15.4%), normal (31.7%), overweight (20.2%), obese I (29.8%), obesity II (2.9%). Similarly, in the frequency of hypotension (1.9%), normal (36.5%), hypertension (34.6%), hypertension I (7.7%), hypertension II (2.9%) . The sample is more overweight, obese than the normal category. For the category of blood pressure more on pre hypertension and hypertension. Thus, excess body mass index can affect the elderly blood pressure. Keywords: body mass index, blood pressure, elderly